Professionally unaligned interpreting in Belgian marriage fraud investigations and its consequences. (2nd January 2021) - Vandenbroucke, Mieke; Defrancq, Bart
ABSTRACT: This paper comprises a comparative empirical analysis of the performance of professional interpreters and informal ad hoc interpreters mediating in marriage fraud investigative interviews. These interviews are particular contexts in which interpreting is needed, as they are hybrid in nature and imply interview encounters in both administration and police contexts and can have legal aftermaths. As Belgian law does not provide guidelines for the type of interpreter required to mediate in these interviews, a high degree of variation is found in the type of interpreter selected and in the handling of ethical issues. Based on our analysis of empirical examples, this variation gives rise to professional interpreters' performance resembling ad hoc or informal interpreting practices with non-normative patterns of turn-taking and footing, non-impartial roles and a definite influence exerted on the selection of information conveyed and entextualised in the report. These practices, some of which are sub-optimal, do not ensure equal treatment and due process as should be expected in a legal-administrative investigation as consequential and high-stakes as a marriage fraud investigation.